A Needs Analysis of Listening Instruction for Nursing Students at Universitas Bunda Thamrin - Natalia W.P. Tarigan (ELT (English Language Teaching Prima Journal), 2025)
Listening comprehension is a critical component of English for Specific Purposes (ESP), particularly for nursing students who must process spoken information accurately in academic and professional healthcare contexts. Despite its importance, listening instruction in many nursing programs remains insufficiently aligned with learners’ actual communicative needs. This study aims to investigate the target listening needs of nursing students at Universitas Bunda Thamrin in relation to their academic studies and future professional responsibilities, as well as to identify the listening difficulties they currently experience in learning English. Adopting a descriptive needs analysis design, the study employs a convergent mixed-methods approach that integrates quantitative data from questionnaires and qualitative data from semi-structured interviews. The needs analysis framework combines Target Situation Analysis (TSA) and Present Situation Analysis (PSA) to examine the gap between students’ current listening competence and the demands of academic and clinical nursing contexts. The findings reveal that nursing students prioritize professional listening needs, such as understanding patient complaints and medical instructions, over general academic listening tasks. Additionally, students experience significant listening difficulties related to limited medical vocabulary, fast speech rate, unfamiliar accents, and listening anxiety. These findings highlight the necessity of designing ESP listening instruction that is context-specific, learner-centered, and grounded in empirical needs analysis. The study contributes to ESP pedagogy by providing evidence-based insights for improving listening curricula in nursing education.